Defining Maritime 4.0: Reconciling principles, elements and characteristics to support maritime vessel digitalisation - Brendan P. Sullivan; Elias Arias Nava; Shantanoo Desai; Jordi Sole; Monica Rossi; Lucia Ramundo; Sergio Terzi (IET Collaborative Intelligent Manufacturing, 2021)
Abstract As complex systems, maritime vessels generate and require the utilization of large amounts of data for maximum efficiency. Designing, developing, and deploying these systems in a digital world requires rethinking how people interact and utilize technology throughout all areas of the industry. With growing interests in Industry 4.0, there are broad opportunities for the incorporation and development of new digital solutions that will support the improvement and optimization of next generation systems. However, while different technologies have been deployed with various levels of success the current challenge is not generating data but being able to harmoniously integrate different data streams into the decision‐making process. To support the development of next generation vessels, a comprehensive understanding of Maritime 4.0 is necessary. Current conceptions of 4.0 within the industry remain ambiguous and based on our research, have demonstrated a divergence in the levels of technological maturity and digital solutions in different industry sectors. This study leverages current state‐of‐the‐art literature and a series of interviews to formulate a descriptive definition of Maritime 4.0 that incorporates technologies that can be integrated to support decision‐making. Through a rigorous, empirically grounded, and contextually relevant approach, the contribution of this study is the establishment of an organized set of technologies and characteristics related to 4.0 and establishment of a practical definition.